Aspek Pemidanaan Korporasi Berdasarkan KUHP 2023 dan Perma Nomor 13 Tahun 2016 - M. Ilham Wira Pratama (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: This study aims to determine the applicability of the criminal aspects of the Supreme Court Regulations concerning the Procedures for Handling Criminal Acts by Corporations when the Indonesian Criminal Code is in force. Methodology/approach: This research is normative legal research, which uses primary legal materials in the form of the Indonesian Criminal Code and Supreme Court Regulation Number 13 of 2016, secondary legal materials in the form of books and various legal research journals, and tertiary legal materials in the form of information obtained from the Internet. The research approach used is statutory and conceptual. The results of the analysis are presented in a qualitative descriptive manner, and conclusions are drawn in the final stage. Results: The criminalization of corporations in the Indonesian Criminal Code strengthens the applicability of the criminalization of corporations in Supreme Court Regulation Number 13 of 2016 concerning Procedures for Handling Criminal Acts by Corporations. Conclusion: PERMA No. 13/2016 regulates the formal and execution aspects of corporate punishment, while Article 56 of the Criminal Code complements it through substantive criminal provisions, thereby strengthening corporate criminal liability in Indonesia. Limitations: The scope of this research is limited to criminal law and the criminal system in corporations in Indonesia. Contribution: This research contributes to the development of knowledge in the field of criminal law and law enforcement, especially regarding the criminal system for corporations.